PETA PRIORITAS PENGEMBANGAN PTAI BERBASIS ANALISIS EVALUATIF PERSPEKTIF BADAN AKREDITASI NASIONAL PERGURUAN TINGGI (BAN-PT) - Susandra, Sony (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2013)
The main mandate of Islamic Higher Education is to offer islamic studies.In its development, islamic studies as a discipline has changed its paradigm not toemphasize on one normative approach only.This paper explains how Islamic Higher Education which has extendedmandate develops. The historical approach to islamic teachings makes IslamicHigher Education open possibility to the study of other disciplines. Thisrelationship often have some tense to come into one representative formula. Thedevelopment of a certain discipline will have a direct implication to thedevelopment of the institution.The evaluation instrument of the development of Higher education isaccreditation. BAN PT applies some standards that sometimes do not match thereal condition of higher education, especially islamic studies-based highereducation.